The Correlations Among Teachers’ Competences, Students’ Learning Motivation, and Students’ English Proficiency - Eka Septiani; Ismail Petrus; Soni Mirizon (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Teachers’ competences and students’ motivation have been long suspected to have influence on students’ English ability. Some studies have been conducted to investigate the relationship. However, some information is unobserved. This study intended to fill the gap in literature concerning the relationship among teacher’s competences, students’ learning motivation, and students’ English proficiency at Junior High Schools in OKUT. The samples of the study were 30 teachers and 918 students. The data were collected through documentation (teachers’ competence test result and students’ English proficiency test result) and questionnaire (students’ learning English motivation). The results showed that there was a significant correlation between the English teachers’ competence and the English proficiency of students showed by robtained = .363, (p=.49) which was higher than the rtable (.361). Then, there was a positive significant correlation between students’ motivation in learning English and their English proficiency achievement (r= .711, p = .000). Meanwhile, the correlation between teachers’ competence and students’ motivation in learning English also showed that there was a positive significant correlation between these variables ( r = .753, p = .000) . At last, the correlation was also found between the predictor variables (teachers’ competence and students’ learning English motivation) and criterion variable (students’ English proficiency) with correlation coefficient 0.758 significant at .01 level. The contributions given by predictor variables to criterion variable were also analyzed. The result of stepwise method showed that predictor variables contributed to 54.4% of the criterion variable. Keywords: teachers’ competences, students’ learning motivation, students’ English proficiency, correlation, contribution